The Potential of Rice Husk Biopellets as a Substitute Fuel - Rusdianasari, Rusdianasari; Kalsum, Leila; Hasan, Abu; Syaritri, Dwi; Arza, Tasya Dwi Putri; Octhaviana, Vivi; Nor, Siti Najdah Binti Mohd; Jamil, Maizun Binti; Risdzuan, Aiman Arif Bin (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
One of Indonesia's greatest waste crops, rice husk, has not yet been fully exploited. Rice husk has a high lignocellulose content, increasing its potential as a renewable energy source, particularly in the form of biopellets. The procedure of creating biopellets is the focus of this study. biopellets made from rice husk and evaluate their quality using proximal, ultimate, value, density, and heat criteria. The study's stages include drying the raw material, milling it to a uniform size, using a pellet mill for pelletisation, and testing the biopellets for quality in compliance with SNI 8951:2020. The study's findings revealed that rice husk biopellets have sufficient calories and low water content after undergoing optimal drying. However, the high relative ash content is the main problem in using it as a feedstock for co-firing, necessitating quality enhancement through chemical treatment or blending with other biomass. Overall, biopellets derived from rice husks have the potential to serve as an environmentally acceptable and cost-effective alternative energy source for household and industrial use. Contribution to Sustainable Development Goals (SDGs): SDG 11: Sustainable Cities and Communities SDG 13: Climate ActionSDG 15: Life on Land